Methodological Recommendation on the Use of Artistic Gymnastics in Physical Education Lessons of General Education Schools - Rayimova Dilnoza Fahkriddinovna (Zien Journals, 2022)
this methodical recommendation is to organize the science of physical education in general education schools and to give a recommendation on the role of rhythmic gymnastics and its use in lessons in educating students to be healthy, well-rounded, fit and attractive.
Keywords: physical culture; sports; rhythmic gymnastics; reproductive health